"It's more than teaching": A qualitative exploration of factors shaping lecturers’ psychological well-being - Kusumowardhani, Retno Pandan Arum (INSPIRA: Indonesian Journal of Psychological Research, 2025)
The worldwide shift in higher education, including stricter performance standards, greater bureaucracy, and the rise of managerial governance models, has a significant impact on academic work. This research investigates the lived experiences and psychological well-being of lecturers in the context of Indonesia's ongoing evolution. Using a qualitative phenomenological approach, in-depth semi-structured interviews were conducted with six lecturers from universities overseen by the Ministry of Education, Culture, Research, and Technology and the Ministry of Religious Affairs. Thematic analysis was used to look at the data. The findings indicate that lecturers perceive psychological well-being as a synergistic condition characterized by inner peace, meaningful engagement with their work, and positive connectivity to their academic environment. Their well-being is shaped by a dynamic interplay among personal, relational, and structural-institutional factors. Participants articulated a clear desire for improved working conditions, institutional support aligned with academic values, and policies that consciously foster well-being. This study contributes to the literature by extending eudaimonic well-being frameworks and the Conservation of Resources Theory into the specific socio-cultural and structural context of Indonesian higher education, highlighting the critical interaction between personal and institutional resources. Practically, the findings underscore the necessity of human-centered academic management, including workload rationalization, the development of supportive leadership, and the formal integration of well-being policies to sustain both lecturer welfare and institutional performance